Contação de histórias e formação de leitores: leitura literária nas séries finais do ensino fundamental. - Cavalcante, Télia Batista (Universidade Federal do Tocantins, 2024)
The teaching of literature in the public network needs strategies that will captivate the readership to appreciate this art. This research, applied in a public school in Palmas - TO, aimed to understand and revise ways of working literary reading, used, to encourage reading in young people and children, the Storytelling. As a strategy we propose to stimulate the participation of the young people of the 9th year of Elementary School in cultural activities, forming them mediators / multipliers. The research focus on the field of the intervention. It was developed with a group of twelve students of the final series in five stages: recruitment; first readings and group interaction; formation of reading mediators - theory; planning / training and presentations. Understanding that reading is extremely important for the social context comprehension and that it is also important that the youth be protagonist in the struggle for a better future, there has been a desire to use this instrument as a way to disseminate the taste for literary art. From the results of this action research it was possible to visualize that a simple process whose students are transforming agents can contribute satisfactorily to cultural, intellectual development, improve interpersonal relations, orality and writing. In order to form this community of readers, we started by reading and studying wonderful tales as a genre focus and we used the logbook to collect the data both on the readings carried out on the course and the record of all the steps seen from each group's perspective. In light of storytelling, literary reading and literary literacy, we work with the notions postulated by Coelho (2006), Busatto (2007), Colomer (2007), Cosson (2018) and Candido (2012).